2006
DOI: 10.1021/jp056486t
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Phenothiazine Compounds with Zwitterionic Lysophosphatidylcholine Micelles:  Small Angle X-ray Scattering, Electronic Absorption Spectroscopy, and Theoretical Calculations

Abstract: In this work, small-angle X-ray scattering (SAXS) studies on the interaction of the phenothiazine cationic compounds trifluoperazine (TFP, 2-10 mM) and chlorpromazine (CPZ, 2-10 mM) with micelles of the zwitterionic surfactant L-R-lysophosphatidylcholine (LPC, 30 mM), at pHs 4.0 and 7.0, are reported. The SAXS results demonstrate that, upon addition of both phenothiazines, the LPC micelle of prolate ellipsoidal shape changes into a cylindrically shaped micelle, increasing its axial ratio from 1.6 ( 0.1 (in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 29 publications
4
35
0
4
Order By: Relevance
“…Altogether, these findings denote that the porphyrin location is favored by both electrostatic and hydrophobic contributions, giving rise to binding constant values that are quite larger as compared to the binding of cationic drugs to HPS micelles [13]. Similar results were also recently obtained for the interaction between cationic phenothiazine drugs and zwitterionic lysophosphatidylcholine (LPC) micelles, noting that the dipole moment component along the methylene chain for HPS and LPC molecules differs significantly in the magnitude and sense [14].…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…Altogether, these findings denote that the porphyrin location is favored by both electrostatic and hydrophobic contributions, giving rise to binding constant values that are quite larger as compared to the binding of cationic drugs to HPS micelles [13]. Similar results were also recently obtained for the interaction between cationic phenothiazine drugs and zwitterionic lysophosphatidylcholine (LPC) micelles, noting that the dipole moment component along the methylene chain for HPS and LPC molecules differs significantly in the magnitude and sense [14].…”
Section: Introductionsupporting
confidence: 82%
“…In a previous study [23], we have reported a similar behavior for SAXS curve from 40 mM of pure SDS micelles at pH 4.0, where a narrow peak at q = 0.04 Å −1 was observed. In the case of 30 mM of both drug-free HPS and LPC micelles [12,14], the SAXS curves were fitted by considering S(q) = 1 in Eq. (1), consistent with the noninteracting zwitterionic micelles due to their null overall charge.…”
Section: Saxs Analysismentioning
confidence: 99%
“…In conclusion, the results of all studies on CPZ (9) and TFP (5) binding to detergent micelles pointed to such a localization of drug molecules in the micelle that the protonated phenothiazine side group was placed near the polar head region of detergent molecules, whereas the hydrophobic ring system was immersed in the interior of the micelle [26].…”
Section: Interaction Of Phenothiazines With Model Systemsmentioning
confidence: 85%
“…The interaction of two phenothiazines, TFP (5) and CPZ (9), with detergent micelles of different character was thoroughly investigated [22][23][24][25][26]. First, the binding of 5 and 9 to cationic, zwitterionic, and neutral detergent micelles was studied by means of absorption spectroscopy [22].…”
Section: Interaction Of Phenothiazines With Model Systemsmentioning
confidence: 99%
See 1 more Smart Citation